1986
DOI: 10.1136/adc.61.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Non-tuberculous mycobacterial lymphadenitis.

Abstract: There were 12 girls and seven boys. All were white, with a mean age of 5-2 years (range 18-9-7 years).Results (Tables 1 and 2) Cervical nodes were the commonest affected (47%) followed by submandibular (31-5%) and preauricular (21%). In 16 (84%) of the children the lymphadenopathy was unilateral. Mean duration of swelling was 6-6 weeks (range 2 weeks-4 months). Appearance of the nodes varied but in 12 (63%) was suggestive of cold abscess with absent or minimal tenderness and fluctuation. Of the other seven, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 12 publications
2
39
1
Order By: Relevance
“…However, lymphadenitis caused by the M. tuberculosis complex seems to adopt a more chronic course compared with lymphadenitis caused by MOTT, which result in a more rapid clinical course (12). In developed countries, MOTT are the most common causes of TBL (36). A report on mycobacterial lymphadenitis from the United States showed that while 95-98z adult patients were infected by M. tuberculosis, 86-92z children were infected by MOTT (M. scrofulaceum, M. avium-intracellulare, and M. kansasii) (14).…”
Section: Etiological Agentsmentioning
confidence: 99%
“…However, lymphadenitis caused by the M. tuberculosis complex seems to adopt a more chronic course compared with lymphadenitis caused by MOTT, which result in a more rapid clinical course (12). In developed countries, MOTT are the most common causes of TBL (36). A report on mycobacterial lymphadenitis from the United States showed that while 95-98z adult patients were infected by M. tuberculosis, 86-92z children were infected by MOTT (M. scrofulaceum, M. avium-intracellulare, and M. kansasii) (14).…”
Section: Etiological Agentsmentioning
confidence: 99%
“…A tuberculous infection usually responds very well to antituberculous chemotherapy, whereas a nontuberculous mycobacterial infection may require a surgical intervention [51,52].…”
Section: Treatmentmentioning
confidence: 99%
“…Four large, retrospective studies have demonstrated that surgical excision of infected nodes has a cure rate between 81% and 92%, which rises to 95% if there is early surgical intervention. (19)(20)(21)(22) A recent, well-conducted trial in which 100 children were randomised to either undergo surgical excision or receive at least 12 weeks of therapy with clarithromycin and rifabutin has shown surgery to be more effective than antibiotic therapy, with cure rates of 96% and 66%, respectively. (23) However, there was a reported complication rate of 28% in children who underwent surgery, which included secondary staphylococcal infection and transient or permanent facial nerve damage.…”
Section: Discussionmentioning
confidence: 99%